2020
DOI: 10.1093/mnras/staa077
|View full text |Cite
|
Sign up to set email alerts
|

The tale of the tail – disentangling the high transverse velocity stars in Gaia DR2

Abstract: Although the stellar halo accounts for just ∼ 1% of the total stellar mass of the Milky Way, the kinematics of halo stars encode valuable information about the origins and evolution of our Galaxy. It has been shown that the high transverse velocity stars in Gaia DR2 reveal a double sequence in the Hertzsprung-Russell (HR) diagram, indicating a bifurcation in the local stellar halo within 1 kpc. We fit these stars by updating the popular Besançon/Galaxia model, incorporating the latest observational results for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
43
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 63 publications
(120 reference statements)
9
43
0
Order By: Relevance
“…There have been many estimates of the space density of thick disk ( f TD ) and halo ( f h ) stars in the solar neighborhood. Early estimates for f h based on star counts have ranged from 0.06 to 0.2% (e.g., Gould et al 1998;Robin et al 2003), though more recent estimates based on spectroscopic studies and kinematic data from the Gaia mission have converged on valuesof ∼0.45% (e.g., Posti et al 2018;Amarante et al 2020). Similarly, the values of f TD have varied, with the most recent estimates ranging from 4% to 7% (e.g., Bland-Hawthorn & Gerhard 2016; Amarante et al 2020).…”
Section: The Space Density Of Early-type Esdtsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many estimates of the space density of thick disk ( f TD ) and halo ( f h ) stars in the solar neighborhood. Early estimates for f h based on star counts have ranged from 0.06 to 0.2% (e.g., Gould et al 1998;Robin et al 2003), though more recent estimates based on spectroscopic studies and kinematic data from the Gaia mission have converged on valuesof ∼0.45% (e.g., Posti et al 2018;Amarante et al 2020). Similarly, the values of f TD have varied, with the most recent estimates ranging from 4% to 7% (e.g., Bland-Hawthorn & Gerhard 2016; Amarante et al 2020).…”
Section: The Space Density Of Early-type Esdtsmentioning
confidence: 99%
“…Early estimates for f h based on star counts have ranged from 0.06 to 0.2% (e.g., Gould et al 1998;Robin et al 2003), though more recent estimates based on spectroscopic studies and kinematic data from the Gaia mission have converged on valuesof ∼0.45% (e.g., Posti et al 2018;Amarante et al 2020). Similarly, the values of f TD have varied, with the most recent estimates ranging from 4% to 7% (e.g., Bland-Hawthorn & Gerhard 2016; Amarante et al 2020). Considering WISEA 0414−5854 and WISEA 1810−1010 likely belong to the thick disk or halo population, if we take 0.45% (7%) as the true fraction of early T dwarfs that belong to the esdT class, the expected number of esdTs within 90 pc is∼10 (∼159).…”
Section: The Space Density Of Early-type Esdtsmentioning
confidence: 99%
“…By selecting stars with v t > 200 km/s, one expects a negligible contamination by thick disk stars. However, with the high quality data provided by Gaia (Gaia Collaboration et al 2016, 2018a, recent studies have shown that such a kinematic cut still leaves a population of stars with thick disk chemistry (Gaia Collaboration et al 2018b;Haywood et al 2018;Amarante et al 2020). This imprint is also seen when different kinematic criteria are * Released on November, XXth, 2019 chosen (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Di Matteo et al (2019) and Amarante et al (2020) found that many counter-rotating stars in the Solar Neighbourhood are too metal-rich to be considered part of the accreted halo. In particular, Di Matteo et al (2019) noted a low angular momentum population with thick disk chemistry (see, e.g., their figure 13) and proposed that the classical Milky Way (MW) inner-halo is actually composed of two stellar populations: i) heated stars from the thick disk (referred by them as the "Plume"), where the heating mechanism is associated with a major merger event named the Gaia-Sausage/Enceladus 1 (Belokurov et al 2018;Helmi et al 2018); ii) accreted stars from the Gaia-Sausage.…”
Section: Introductionmentioning
confidence: 99%
“…In the following section we briefly introduce a new modelling procedure which enables us to estimate the f h and f T D from the data and thus quantify the expected thick disc contamination. The full analysis of this sample, including its chemistry and dynamics, can be found in (Amarante et al 2020).…”
Section: Introductionmentioning
confidence: 99%